AlAhnaf Alyamani who died before 717 Hijri, and his book Albstan Fi Ia,rab Mshklat Alkra,n between renewal and imitation - Al-Barqi, Ali Sulaiman (Journal of Humanities & Social Sciences, 2019)
This research aims at shading the light on this linguist who was not given the consideration he deserves, especially that he lived in relatively early era , and presenting th rich scientific material that was stipuilated within the book contents, and emphasizing on the author linguistic efforts while providing tha reader a brief on Yemenis Linguists at that era and attempting to further understand tha level to which tha Linguists reached then, in addition to implying about Quran Linguistic science and its main literature, and the author followed induction approach than explanation and analysis that led to many results mainly the unique terms that the author delivered and isolating himself from his contemporary and predecessor authors at different regions at that era and his dependence on original sources in general.
Keywords: Al-Ahnaf Al-Yamani; Al-Bustan in parsing the problems of the Qur’an; grammatical and inflectional; imitation and renewal